PENINGKATAN HASIL BELAJAR IPAS MENGGUNAKAN MEDIA POP-UP BOOK PADA SISWA KELAS V SD NEGERI 07 KOTO BALINGKA KABUPATEN PASAMAN BARAT - Zahra, Jolina; Shilfia Iraqi, Hana; Safitri, Serly; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low Science and Social Studies (IPAS) learning outcomes of fifth-grade students at SD Negeri 07 Koto Balingka, West Pasaman Regency. Preliminary data showed that only 10 of 19 students (52.6%) achieved the Learning Achievement Criteria (KKTP) of 75, while 9 students (47.3%) had not reached mastery. This condition was caused by the suboptimal use of learning media, teacher-centered instruction, and low student involvement in the learning process. This study aimed to describe the improvement of IPAS learning outcomes through the use of Pop-Up Book media combined with the Problem Based Learning (PBL) model, covering lesson planning, implementation, and student learning outcomes. This study was a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles; Cycle I consisted of two meetings (June 11 and 15, 2026) and Cycle II consisted of one meeting (June 18, 2026). The subjects were 19 fifth-grade students in the second semester of the 2025/2026 academic year. Data were collected through interviews, observation, tests, and documentation, then analyzed qualitatively and quantitatively. The results showed: (1) lesson planning was developed as a teaching module aligned with the Merdeka Curriculum; (2) learning implementation improved, shown by average teacher activity from 76.78% (Good) in Cycle I to 89.28% (Very Good) in Cycle II; and (3) student learning outcomes improved in knowledge, attitude, and skill aspects, with the average knowledge score rising from 77.37 (classical mastery 73.65%) in Cycle I to 82.10 (classical mastery 84.2%) in Cycle II. Thus, the use of Pop-Up Book media through the Problem Based Learning model can improve the IPAS learning outcomes of fifth-grade students.